Wealth effect and macroeconomics factors of a firm’s international merger and acquisition exercise: empirical evidence from multinational firms - Amin Noordin, Bany Ariffin; Kamarudin, Fakarudin; Mohamad Anwar, Nazratul Aina (Kaunas University of Technology, 2015)
The aim of this study is to examine the influence of macroeconomic factors on the wealth effects of international merger and acquisitions by Malaysian multinational companies (MNCs). There are three macroeconomics factors: foreign economic condition, gross national product (GNP) correlation between countries and the level of the economic development of a target country. A random sample of 165 international mergers and acquisitions by Malaysian bidding MNCs in 22 countries around the world in the period of 2000–2010 was recruited for this study. A negative relationship between the foreign economic condition and the wealth effect and a positive relationship between the level of economic development of target country and the wealth effect has been found through this study. This implies that the foreign economic condition and level of economic development of the target country significantly determine the value creation of the Malaysian cross-border acquisitions. Therefore, Malaysian MNCs, which intend to use the acquisition mode of entry as the way to venture abroad, should take into consideration these macroeconomic factors in order to increase their foreign investment value.